2015
DOI: 10.1111/lam.12397
|View full text |Cite
|
Sign up to set email alerts
|

Xylanases of Bacillus spp. isolated from ruminant dung as potential accessory enzymes for agro-waste saccharification

Abstract: The uncontrolled use of fossil fuels and concerns about its future availability, have invoked interest over unconventional alternative energy sources like solar, hydropower, geothermal, nuclear and biomass. Plants, being largest renewable biomass on earth, have received consideration as a source of biofuels. Ruminant dung isolates M35, R31 and J208 belonging to Bacillus sp. produces majorly endo-xylanase when induced with wheat bran. Such plant cell wall degrading endo-xylanases with broad pH optima and mesoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…While applications of the acidic pectinases and alkaline pectinases are limited in food and textile industries, respectively, the stability of pectinases from the three Bacillus isolates in mild acidic to moderate alkaline pH would be an asset to varied applications considering their mesophilic nature. Xylanolytic activity suitable for agrowaste saccharification from these isolates B. safensis M35 , B. altitudinis R31 and B. altitudinis J208 has been reported earlier in the temperature range of 30–60°C and pH range of 5·0–9·0 (Thite and Nerurkar ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While applications of the acidic pectinases and alkaline pectinases are limited in food and textile industries, respectively, the stability of pectinases from the three Bacillus isolates in mild acidic to moderate alkaline pH would be an asset to varied applications considering their mesophilic nature. Xylanolytic activity suitable for agrowaste saccharification from these isolates B. safensis M35 , B. altitudinis R31 and B. altitudinis J208 has been reported earlier in the temperature range of 30–60°C and pH range of 5·0–9·0 (Thite and Nerurkar ).…”
Section: Discussionmentioning
confidence: 72%
“…). In our earlier work, the crude xylanases produced by xylano‐pectinolytic Bacillus safensis M35, Bacillus altitudinis R31 and B. altitudinis J208 isolated from ruminant cattle dung were shown to act as accessory enzymes in a cocktail with commercial cellulase Primafast ® 200 (Thite and Nerurkar ). Interestingly, these three Bacillus isolates also showed pectinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Once the system was cooled down to room temperature, DW was added to make volume up to 1.5 ml and A 540 nm was measured. One unit of xylanase activity was defined as the amount of xylanase required to release an end product equivalent to one µmol of D-xylose in reaction mixture per unit time in optimum incubation conditions 3,15 .…”
Section: Bacterial Strains and Media Used For Enzyme Production Bacimentioning
confidence: 99%
“…These strains have been shown to produce an endo-xylanase, and three types of endo-pectinases i.e., polygalacturonate hydrolase (PGase), pectate lyase (PL) and pectin lyase (PL). Studies on the physico-chemical properties of these enzymes during our earlier work revealed diverse characteristics along with their cellulase free feature imparting industrial importance to these enzymes 3,4 . The accessory potential of these cellulase free xylanase and pectinase enzymes to the commercial cellulase has been proven through the enzyme cocktail mediated saccharification of raw and pretreated agrowaste biomass 5,6 .…”
mentioning
confidence: 99%
See 1 more Smart Citation